2022
DOI: 10.1007/s13385-022-00318-0
|View full text |Cite
|
Sign up to set email alerts
|

The slowdown in mortality improvement rates 2011–2017: a multi-country analysis

Abstract: Mortality rates have been falling or ‘improving’ in many demographically developed countries since the 1950s. However, there has been a slowdown since 2010 in the speed of improvement and this phenomenon has been particularly marked at ages over 50. To understand better this mortality slowdown, we have analysed long-run mortality trends of a group of developed countries using data up to 2017 from the Human Mortality Database. Specifically, we have used statistical models to parametrise the historical mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
4
5
0
Order By: Relevance
“…Visual inspection showed that a second order polynomial usually gave the best estimate for the 'average' or 'baseline' deaths in 2019although in most instances the actual differences are minor. This is consistent with the observation that there was a break point in international mortality improvement from 2011 onward [44]. Exceptions include infants in the first year of life where population-adjusted male and female mortality was constant between 2013 and 2019.…”
Section: Estimation Of Year Of Age Baseline For Deaths In England And...supporting
confidence: 90%
See 2 more Smart Citations
“…Visual inspection showed that a second order polynomial usually gave the best estimate for the 'average' or 'baseline' deaths in 2019although in most instances the actual differences are minor. This is consistent with the observation that there was a break point in international mortality improvement from 2011 onward [44]. Exceptions include infants in the first year of life where population-adjusted male and female mortality was constant between 2013 and 2019.…”
Section: Estimation Of Year Of Age Baseline For Deaths In England And...supporting
confidence: 90%
“…These two sources were used to cross-check each other, and the full detail is given in the Supplementary Materials S2-S5 [38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Validation Of Deaths 'Due To' Covid-19 and Methods For Adjus...mentioning
confidence: 99%
See 1 more Smart Citation
“…Global life expectancy has shown a dramatic increase over the last century in most high-income countries (HICs) even though these mortality declines have not been universal between and within populations. 1 In the years preceding the Covid-19 pandemic, there were observed slowdowns in longevity improvements or even mortality reversals in some HICs [2][3][4][5][6] corresponding to warning signs for both longstanding and emerging health problems. 7 The Covid-19 pandemic has had a further dramatic impact on longevity globally including in HICs.…”
Section: Introductionmentioning
confidence: 99%
“…Life expectancy is an objective measure of a population´s health and relies on a complex variety of individual, social, economic and regional factors [ 1 5 ]. Although the life span with the interruption of World War II has risen globally over the last 100 years, the decline in mortality has recently slowed down in developed countries despite major increases in health expenditure [ 6 8 ]. Also, there is robust evidence from European countries that the overall gain in life span appears to be dearly bought by an increase in disabled years [ 9 ].…”
mentioning
confidence: 99%